Invasive Pulmonary Aspergillosis in a Sickle Cell Patient Transplant Recipient: A Successful Treatment - Katia Paciaroni; Gioia De Angelis; Cristiano Gallucci; Cecilia Alfieri; Michela Ribersani; Andrea Roveda; Antonella Isgrò; Marco Marziali; Ivan Pietro Aloi; Alessandro Inserra; Javid Gaziev; Pietro Sodani; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle Cell Anaemia (SCA) is the most common inherited blood disorder and is associated with severe morbidity and decreased survival. Allogeneic Haematopoietic Stem Cell Transplantation (HSCT) is the only curative approach. Nevertheless the decision to perform a marrow transplant includes the risk of major complications  and mortality transplant related. The infections represent the main cause of mortality for SCA patients undergoing transplant. Invasive Pulmonary Aspergillosis (IPA) is a devastating opportunistic infection and remains a significant cause of morbidity and mortality in HSCT recipients. Data regarding IPA in the setting of SCA are lacking. In the present report,  we describe a patient with SCA who developed IPA after allogeneic bone marrow transplant. The fungal infection was treated by systemic antifungal therapy in addition to the surgery, despite  mild chronic GVHD and with continuing immunosuppression therapy. This case shows that IPA occurring in bone marrow recipient with SCA can be successful treated